Research Progress on the Anticancer Activities and Mechanisms of Polysaccharides From Ganoderma - Wang, Man; Yu, Fei (Frontiers in Pharmacology, 2022)
Cancer ranks as a primary reason for death worldwide. Conventional anticancer therapies can cause severe side effects, and thus natural products may be promising drug candidates for cancer therapy. Accumulating evidence has verified the prominent anticancer properties of Ganoderma polysaccharides, suggesting that Ganoderma polysaccharides may be effective chemopreventive agents of natural origin. Based on their abilities to prevent cancer development by regulating the DNA damage response, cancer cell proliferation, apoptosis, host immunity, gut microbiota and therapeutic sensitivity, there has been increasing interest in elucidating the clinical implication of Ganoderma polysaccharides in cancer therapy. In this review, we summarize recent findings pertaining to the roles of bioactive polysaccharides from Ganoderma in cancer pathogenesis, discuss the multifarious mechanisms involved and propose future directions for research. A more sophisticated understanding of the anticancer benefits of Ganoderma polysaccharides will be helpful for improving current treatments and developing novel therapeutic interventions for human malignancies.